The Effectiveness of Assertiveness Training Group Format to Improve Students' Interpersonal Relationship Skills - Lubis, Khadijah (Bisma The Journal of Counseling, 2020)
Interpersonal relationship skills are the ability of individuals to build relationships with other people. This research is motivated by the discovery of interpersonal relationship problems among students, such as being unable to refuse invitations from friends, isolated students, muttering, aggressive, and a lack of care for others. This study aims to test the effectiveness of assertiveness group format training to improve students' interpersonal relationship skills. This study used a quasi-experimental method with the non-equivalent control group design. The subjects of this study were students of class VIII SMP who were selected by purposive sampling technique. The instrument used was a scale of interpersonal skills with a validity of 0.535 and reliability of 0.881. Data analysis used the wilcoxon signed-rank test and kolmogorov smirnov. The results showed that the use of assertiveness training group format was effective in improving students' interpersonal relationship skills.